ANALYSIS OF DROUGHT CONDITIONS IN ARMENIA IN JUNE 2021 USING OBSERVATIONAL AND SATELLITE DATA (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
In June 2021, the RA experienced an unprecedented high temperature for 1961–1990 – 4.2℃ above normal (13.4℃). The recorded rainfall (71 mm) was significantly below normal (27%). The article presents maps of precipitation distribution in the territory of the Republic of Armenia in June, a comparison of satellite data and station data, as well as maps that show drought conditions.
Keywords: temperature; moistening of the territory; atmospheric precipitations; drought; drought index